Electrochemical performance of NiCo2O4 and NiCo2O4/Ti3AlC2 composite for supercapacitor applications - Shahid M Ramay; Mohammed H Aldosary (Materials Research Express)
Supercapacitors are pivotal for the advancement of energy storage technologies, offering unparalleled power density and rapid charge–discharge cycles essential for modern electronic and automotive applications. Combining different materials is a powerful approach to enhancing the electrochemical properties of each constituent. In the current report, we examine the structural, morphological, and electrochemical characteristics of pure NiCo _2 O _4 and NiCo _2 O _4% -5% Ti _3 AlC _2 composite. The pristine NiCo _2 O _4 is fabricated utilizing the Sol–Gel auto-combustion route, while its composite NiCo _2 O _4% -5% Ti _3 AlC _2 is prepared in ethanol using the ultrasonic process. Structural analysis confirms the existence of the cubic spinel phase of NiCo _2 O _4 with the Fd $\mathop{3}\limits^{\unicode{773}}$ m space group. Surface morphological analysis reveals a distribution of well-defined particles with a decrease in particle size from 50–40 nm. Elemental analysis confirms the purity of the sample by the presence of stoichiometric amounts of the elements. Electrochemical analysis of the studied composite exhibits superior electrochemical properties. Specifically, the highest specific capacitance of 129. 62 F g ^−1 for pure NiCo _2 O _4 and 126.82 F g ^−1 for NiCo _2 O _4 -5% Ti _3 AlC _2 composite is achieved at 2 mA g ^−1 current density. However, the addition of 5% Ti _3 AlC _2 in NiCo _2 O _4 improved its energy density by 27%. Additionally, NiCo _2 O _4 –5% Ti _3 AlC _2 material demonstrated excellent capacitance retention, maintaining 87% after 8000 charge–discharge cycles. These findings show the potential of the studied composite for supercapacitor electrode materials for electrochemical energy storage.